A new wave of migration from Turkey:|An exploration of driving forces - Akpınar, Elif. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Migration is a recurring topic throughout history, caused by different factors at different times, and has been spotlighted by different disciplines like sociology, economics, international relations, and psychology. The term “migration” includes a number of related aspects, from the decision to migrate through the integration (or non-integration) process and even further. There is a huge literature encompassing the theoretical framework and historical data of migration. Migration has always been embedded in Turkey’s history, though the reasons for moving, groups of people who move and destinations have changed over time. Starting with the establishment of the Turkish Republic, national and international movements have helped to shape the country. Almost every decade has had its own migration pattern, formed by various micro- and macro- level determinants. For the last few years, international migration has again become a popular topic among Turkish society. Numbers and destinations are publicized via statistics, the reasons and motivations behind this phenomenon are intensely discussed. This thesis aims to contribute to this literature by suggesting a few factors that are related to willingness to migrate, making use of a survey completed in 2018.
Keywords: Migration -- Social aspects -- Turkey.